Analgesic and neuromotor effects of two extracts of Zanthoxylum rhoifolium (Rutaceae) in the Swiss albino mouse (Mus musculus) - Villegas-Valencia, Melany; González-Reyes, Libardo Andrés; Asencio-Santofimio, Helberg; Gutierrez-Montes, Jose Oscar; García, Angelica; Garzón-Gaviria, Silverio (Vitae, 2020)
BACKGROUND: Colombia has a high diversity of medicinal plants, including Tachuelo (Zanthoxylum rhoifolium), a tree belonging to the family Rutaceae, which has been attributed an analgesic use by communities of the Colombian southwest. Nevertheless, this species has been scarce studied in Colombia. The studies have been limited to the isolation of compounds with antifungal and insecticide activity, using the leaves, branches, and bark of the plant in aqueous, and organic extracts. Neither pharmacological tests have been carried out, nor the analgesic and neuromotor activity have been tested from preparations with this plant’s fruits. OBJECTIVES: To evaluate the analgesic and neuromotor effect of the aqueous and hexane extract of the fruits of Z. rhoifolium. METHODS: As there were no preliminary reports of this study, the first observation was made through Irwin’s test. The formalin and the rotarod test were performed to determine the analgesic and motor coordination effects, respectively. RESULTS: All the evaluated treatments demonstrated to generate analgesia, anesthesia, passivity, reduction in the alarm reaction, and have antinociceptive activity in the formalin test; while only the high dose of the nonpolar extract generated a deficit in the motor performance of the rodents in the rotarod test. CONCLUSIONS: the antinociceptive effect of the aqueous and hexane extracts of this species’ fruits was demonstrated. The hexane extract generated a neuromotor effect, which validates the ethnobotanical reports on Z. rhoifolium fruits.